PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA DAN INSENTIF TERHADAP KINERJA GURU SMK BINA SEJAHTERA 1 KOTA BOGOR - Jubaedah, Bedah; Jahani (Jurnal Gici Jurnal Keuangan dan Bisnis, 2025)
Teacher performance is a crucial factor in determining educational success. Every educational institution has a leader, the principal. Each principal has a different leadership style. This style influences their subordinates and even determines the success of the school they lead. Work motivation and incentives are crucial for teachers in carrying out their duties. The aim of studying is to analyze the influence of the principal's leadership style, work motivation, and incentives on teacher performance at SMK Bina Sejahtera 1 Bogor City. Teacher performance is a key factor in improving educational quality, so it is important to understand the factors that influence it. This study used descriptive and analytical methods with a quantitative approach. A random sampling technique was used to obtain a sample of one hundred people consisting of educators and educational staffs at SMK Bina Sejahtera 1 and 3 Bogor City. The research method used was a quantitative method with a survey approach. The population in this study were all teachers of SMK Bina Sejahtera 1 and 3 Bogor City, and the sample was determined using a purposive sampling technique. Data collection was carried out through a questionnaire that had been tested for validity and reliability. Data analysis used multiple linear regression. The results showed that leadership style had a positive, but not significant, effect. This occurs when a leader can influence the performance of his subordinates, but must be encouraged by good communication skills to all subordinates. Work motivation has a positive, but not significant, effect. This occurs when someone is encouraged to improve their performance, but it depends on the strength of that encouragement. Incentives have a positive and significant effect on performance. This is because when a leader provides incentives to a subordinate who has achieved good performance, they demonstrate the importance of the principal's role, competence in communication, and school management in addressing aspects of leadership, work motivation, and appropriate rewards for performance to improve the performance of educators.